Effect of viral, reservoir, host, and environmental factors on viral evolution that affect morbidity and mortality of COVID-19 disease - Jemima Lewi Santoso (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2023)
The COVID-19 pandemic has been going on for more than two years. The number of sufferers of this disease continues to increase as well as those who die. The number of disease and death cases varies in each country and even in one country in certain seasons and certain tribes. This is triggered by the evolution of viruses that create new variants with different virulences so that they can affect the transmission of the COVID-19 virus. Several factors can trigger the evolution of the virus, one of which is the ability to mutate to create new variants and/or new strains that cause differences in morbidity and mortality due to early COVID-19 strains. Other factors that favor viral evolution are the reservoir, host immunity, and extreme environmental conditions. This is supported by differences in the percentage of morbidity and mortality in various countries. This literature review aims to determine the effect of viral, reservoir, host, and environmental factors (season and rainfall, temperature, sunlight, materials around the environment, animal habitat, water, and wastewater) on the evolution of viruses that affect morbidity and mortality in COVID-19 disease.